Impact of green human resource management practices on the environmental performance of green hotels - Irani, Foad; Kilic, Hasan; Adeshola, Ibrahim (Routledge Journals, Taylor & Francis Ltd, 2022)
This research aims to investigate whether green hotels' environmental performance might improve through staff environmental commitment and green process innovations. Data were obtained from a survey questionnaire conducted with employees of 409 green hotels operating in Turkey. The PLS-SEM technique was adopted using Smart-PLS software to examine the proposed hypotheses. The results verified that green human resource management (GHRM) practices produce a higher level of environmental performance when employee environmental commitment and green process innovations are deployed. Therefore, this study suggests that green hotel management should promote GHRM practices throughout their organizations to enhance employee involvement in environmentally sustainable activities. It adds particularly to a new line of study focused on understanding the essential role of GHRM practices in improving the environmental performance of green hotels.
Keywords: GHRM practices; employee environmental commitment; green process innovation; environmental performance; green hotels; Turkey